Geriatric patient profile and mortality-associated factors in a population over 80 years with COVID-19 infection: an experience of a university hospital in Bogotá - González Sanabria, Jennifer (2022)
Objective: To characterize the geriatric patient profile and identify the mortality-associated factors in a population over 80 years hospitalized with COVID-19 infection in the geriatric ward of a university hospital in the city of Bogotá.Materials and methods: An analytical observational retrospective cohort study based on chart reviews was conducted. The study included patients over 80 years with confirmed COVID-19 infection from March 1, 2020 to February 28, 2021. The dependent variable was mortality and the independent variables were age, clinical factors, baseline characteristics and paraclinical status.Results: Two hundred eighty (280) patients with a median age of 84 years, most of whom were overweight, were identified. The most frequent symptom was cough followed by dyspnea. Out of all patients, 60.3 % presented lymphopenia and elevated D-dimer levels (> 1,000 μg/L), and most of them showed typical imaging patterns of COVID-19. Mortality accounted for 41.4 % and was mainly associated with older age, elevated C-reactive protein, activities of daily living impairment, history of major neurocognitive disorder, comorbidity, and dependent and frail patient profiles.Conclusions: The geriatric population has an increased risk of mortality from COVID-19 infection. The present study